White Opaque Substance, a New Optical Marker on Magnifying Endoscopy: Usefulness in Diagnosing Colorectal Epithelial Neoplasms - Kazutomo Yamasaki; Takashi Hisabe; Kenshi Yao; Hiroshi Ishihara; Kentaro Imamura; Tatsuhisa Yasaka; Hiroshi Tanabe; Akinori Iwashita; Toshiharu Ueki (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims A white substance that is opaque to endoscopic light is sometimes observed in the epithelium during narrowband imaging with magnifying endoscopy of gastric or colorectal epithelial neoplasms. This prospective observational study aimed to determine whether the morphology of the white opaque substance (WOS) allows differential diagnosis between colorectal adenoma and carcinoma. Methods A consecutive series of patients with colorectal adenomas or early carcinomas who underwent endoscopic resection or surgical excision were studied. The morphology of the WOS was determined based on endoscopic images before the histopathological diagnosis was performed. The primary outcome was the diagnostic performance of an irregular WOS as a marker of colorectal carcinoma. Results The study analyzed 125 lesions. A total of 33 lesions showed an irregular WOS, and 92 lesions showed a regular WOS. Among the 33 lesions found to show an irregular WOS, 30 were carcinomas. Among the 92 lesions showing a regular WOS, 79 were adenomas. With irregular WOS as a marker of carcinoma, the diagnostic accuracy was 87%, sensitivity was 91%, and specificity was 86%. Conclusions This study demonstrated the potential usefulness of the morphology of the WOS as a marker for the differential diagnosis between adenoma and carcinoma in cases of colorectal epithelial neoplasms.